Excellent Stability of Perovskite Solar Cells Encapsulated With Paraffin/Ethylene-Vinyl Acetate/Paraffin Composite Layer - Long, Biyu; Zhou, Xianzi; Cao, Huafeng; Chen, Renjie; He, Nannan; Chi, Lina; Fan, Penghui; Chen, Xiaohong (Frontiers in Materials, 2022)
Superior encapsulation technology is important for PSCs to prolong their lifetime and realize their commercial application. Paraffin/EVA/paraffin composite encapsulated layers were fabricated with the ambient environment under the thermal temperature of 80°C, which has advantages for simple procedures and low cost. PSCs encapsulated with paraffin/EVA/paraffin and pure EVA layers maintained 95 and 45% of the initial power conversion efficiency (PCE) aged for 1000 h at RH 75%, respectively. Paraffin/EVA/paraffin-encapsulated PSCs were immersed in water for 5 h, which remained 98% of the original PCE, which is far superior to EVA-encapsulated PSCs. High melting point paraffin at 68°C shows better encapsulation than low melting point (60 and 55°C) paraffin, indicating that the high molecular weight of paraffin helps improve the encapsulation performance of PSCs. PSCs encapsulated with paraffin/EVA/paraffin showed better stability of Voc than pure EVA layer because paraffin can inhibit defects, voids, and edges of metal electrodes that quickly expand, and decay. Therefore, paraffin/EVA/paraffin combination encapsulation is an effective strategy, which can form continuous and dense hydrophobic composite encapsulation films with a friendly metal electrode.